1973
DOI: 10.1002/mrc.1270050906
|View full text |Cite
|
Sign up to set email alerts
|

Struktur‐Reaktivitätsuntersuchungen mit heterosubstituierten Nitrilen—VII:13C‐, 14N‐ und 19F‐NMR‐Spektroskopische Untersuchungen an Verbindungen vom Typ ArXCN

Abstract: Abstract-The chemical shifts of aromatic nitriles of the general structure pnru-Y-C&-X-CN with X = 0, S, Se and N(CH3) have been investigated by the 13C NMR technique. For cyanates (X = 0) the 14N shifts and for Y = F the 19F shifts were likewise measured. The chemical shifts and the corresponding 13C shift increments A, have been found to correlate with the appropriate substituent constants uRo, oDo and oI, as well as with the n-electron densities calculated in the PPP approximation.Zusarnmenfassung-An aromat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
11
0

Year Published

1978
1978
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 30 publications
2
11
0
Order By: Relevance
“…17 Interestingly, covalent cyanates are hardly studied by NMR spectroscopy and we have not found 13 C-NMR data for alkyl cyanates in the literature. The 13 C chemical shift of the cyanato group in aryl cyanates, between 107.9 and 109.9, 22 is in agreement with the observed value of 111.2 ppm.…”
Section: Resultssupporting
confidence: 90%
“…17 Interestingly, covalent cyanates are hardly studied by NMR spectroscopy and we have not found 13 C-NMR data for alkyl cyanates in the literature. The 13 C chemical shift of the cyanato group in aryl cyanates, between 107.9 and 109.9, 22 is in agreement with the observed value of 111.2 ppm.…”
Section: Resultssupporting
confidence: 90%
“…In this case, part of the error may be due to association effects in the neat phenylcyanate used in the experimental measurements. 118 Although MB3 reproduces variations in the 2 Ž chemical shifts of sp carbons fairly well 110 to . 220 ppm relative to methane; see Fig.…”
Section: Carbonmentioning
confidence: 97%
“…The chemical shift (δ 110.05) is comparable to the reported values for cyanato compounds. 13 The presence of cyanoxythiocarbamate group justified the remaining three double bonds in the molecule. Moreover, the chemical shift of the NH proton (δ 7.95, t, J ) 5.0 Hz) revealed that this is cis to sulfur, and the molecule as a whole has a trans (E) stereochemistry as observed earlier in case of thiocarbamates.…”
mentioning
confidence: 99%
“…The molecular formula C 15 H 18 N 2 O 6 S was determined through integration of 1 H-NMR spectrum (Table 1), 13 C-NMR data (broad band and DEPT) ( Table 1), and HREIMS, which showed diagnostic ions at m/z 147.0649 and m/z 207.0247 corresponding to the fragments a (C 6 H 11 O 4 ) and b (C 9 H 7 N 2 O 2 S), respectively.…”
mentioning
confidence: 99%
See 1 more Smart Citation